Using the Chat Generative Pre-trained Transformer in academic writing in health: a scoping review - Isabelle Cristinne Pinto Costa; Murilo César do Nascimento; Patrícia Treviso; Lucélia Terra Chini; Bartira de Aguiar Roza; Sayonara De Fátima Faria Barbosa; Karina Dal Sasso Mendes (Universidade de São Paulo, 2024)
Objective: to map the scientific literature regarding the use of the Chat Generative Pre-trained Transformer, ChatGPT, in academic writing in health. Method: this was a scoping review, following the JBI methodology. Conventional databases and gray literature were included. The selection of studies was applied after removing duplicates and individual and paired evaluation. Data were extracted based on an elaborate script, and presented in a descriptive, tabular and graphical format. Results: the analysis of the 49 selected articles revealed that ChatGPT is a versatile tool, contributing to scientific production, description of medical procedures and preparation of summaries aligned with the standards of scientific journals. Its application has been shown to improve the clarity of writing and benefits areas such as innovation and automation. Risks were also observed, such as the possibility of lack of originality and ethical issues. Future perspectives highlight the need for adequate regulation, agile adaptation and the search for an ethical balance in incorporating ChatGPT into academic writing. Conclusion: ChatGPT presents transformative potential in academic writing in health. However, its adoption requires rigorous human supervision, solid regulation, and transparent guidelines to ensure its responsible and beneficial use by the scientific community.